Crossmodal Associations with Olfactory, Auditory, and Tactile Stimuli in Children and Adults. (November 2021) - Speed, Laura J.; Croijmans, Ilja; Dolscheid, Sarah; Majid, Asifa
People associate information with different senses but the mechanism by which this happens is unclear. Such associations are thought to arise from innate structural associations in the brain, statistical associations in the environment, via shared affective content, or through language. A developmental perspective on crossmodal associations can help determine which explanations are more likely for specific associations. Certain associations with pitch (e.g., pitch–height) have been observed early in infancy, but others may only occur late into childhood (e.g., pitch–size). In contrast, tactile–chroma associations have been observed in children, but not adults. One modality that has received little attention developmentally is olfaction. In the present investigation, we explored crossmodal associations from sound, tactile stimuli, and odor to a range of stimuli by testing a broad range of participants. Across the three modalities, we found little evidence for crossmodal associations in young children. This suggests an account based on innate structures is unlikely. Instead, the number and strength of associations increased over the lifespan. This suggests that experience plays a crucial role in crossmodal associations from sound, touch, and smell to other senses.